An analysis of accuracy quality in translating Diana's Utterances - Putra, Dhanu Ario; Sembiring, Silvia; Monike, Rike; Ependi, Selviyan (UNIVED Press, Universitas Dehasen Bengkulu, 2020)
Translation is an activity to interpreting utterances from source language to the target language without changing the content of the translated utterances. This research aims to find out the translation accuracy of google translate in translating speech spoken by Diana in Wonder woman (2017). The data in this study was conducted using qualitative methods. There was one utterances for each utterances which was divided into 25 and procedure utterances in “Wonder woman” was divided into 30 sentences. The data using the accuracy rating assessment which consist of three categories namely accurate, less accurate, not accurate. The researcher took three raters in evaluating the output of google translate. The result shows that the accuracy of Google translate in translating utterances is accurate with average value of 89%, less accurate is 8%, and not accurate is 3%. And procedure utterances is accurate with average value of 77%, less accurate is 20%, and not accurate is 3%. It can be concluded that Google translate is more accurate in translating utterances with 89%, whereas the procedure utterances is 77%. Keyword: translation accuracy, google translate, utterances